THE EFFECT OF USING LETTER-FISHING MEDIA ON LETTER RECOGNITION ABILITY AND LEARNING INDEPENDENCE OF CHILDREN AT RA KEBUN ILMU - Kamalasari, Kamalasari; Sujarwo, Sujarwo (Universitas Tanjungpura, 2025)
Letter recognition is a fundamental aspect of early childhood literacy. This study aims to analyze the effects of fishing-letter media and poster media on children